PEMANFAATAN DAUN KELOR SEBAGAI BAHAN PANGAN UNTUK MENINGKATKAN GIZI BALITA - Nirwana, Betanuari Sabda; Nikmah, Anis Nikmatul; Awatiszahro, Alfika; Rofiah, Khofidhotur; Wahyuni, Ida Tri (Abdi Panca Marga, 2024)
Nutritional problems for toddlers will arise if the food intake consumed does not match the nutritional needs of toddlers. Nutritional problems that commonly arise include malnutrition and malnutrition. The prevalence of malnutrition and malnutrition among children under five in Indonesia is increasing compared to 2010 to 2019. The number of children under five with malnutrition and malnutrition in Indonesia in 2019 was 19.6% and it is estimated that there are still 4.5 million children under five with malnutrition and malnutrition. less has not been detected. The aim of this community service is to increase the knowledge and skills of mothers of toddlers to use Moringa leaves as an additional food ingredient to improve toddler nutrition. Moringa leaves contain many nutrients and are a source of vitamins and minerals for the body, so they are good for use as a food additive for toddlers. This community service activity was carried out at the Posyandu in Kawedusan Village, Plosoklaten District, Kediri Regency. This activity provides health education and skills in making food menus using Moringa leaves to 25 mothers of toddlers. Evaluation of success was assessed by a post test given to mothers of toddlers. The results of the activity showed that there was an increase in knowledge and skills about the benefits of Moringa leaves for mothers of toddlers with an assessment of knowledge and skills in the good category, namely 8% during the pre-test, after health education and skills in processing Moringa leaves, the post-test results were in the good category, 84%. The conclusion of this community service activity was an increase in the knowledge and skills of mothers of toddlers in understanding the importance of nutrition for toddlers and how to make toddler food menus using Moringa leaves. Keywords : Moringa leaves, improving nutrition, toddler nutrition